2016
DOI: 10.1002/jcb.25534
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fatty Acid Composition in Bone Marrow Fluid From Postmenopausal Women: Modification After Hip Fracture

Abstract: Bone marrow adipose tissue (BMAT) is associated with low bone mass, although the functional consequences for skeletal maintenance of increased BMAT are currently unclear. BMAT might have a role in systemic energy metabolism, and could be an energy source as well as an endocrine organ for neighboring bone cells, releasing cytokines, adipokines and free fatty acids into the bone marrow microenvironment. The aim of the present report was to compare the fatty acid composition in the bone marrow supernatant fluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 43 publications
(57 reference statements)
3
28
2
Order By: Relevance
“…Our result showing the association between NMR measured unsaturation level with BMD was in contrast to two previous studies that found no significant difference in marrow fat composition in subjects with different BMD using gas chromatographers (16, 17). This difference in experimental findings may result from differences in the quantification methods, different sensitivity and reproducibility of the techniques, differences in specimen location and preparation, and differences in study cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our result showing the association between NMR measured unsaturation level with BMD was in contrast to two previous studies that found no significant difference in marrow fat composition in subjects with different BMD using gas chromatographers (16, 17). This difference in experimental findings may result from differences in the quantification methods, different sensitivity and reproducibility of the techniques, differences in specimen location and preparation, and differences in study cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…The unsaturation level quantified using HRMAS 1 H-NMR showed a large range from 15.3% to 51.8%. This unsaturation level was in the range, but with lower average values as compared to previous studies that quantified marrow fat composition using gas chromatography (GC) (16, 17). This under estimate of unsaturation level of NMR methods as compared to GC was consistent with the report from Yeung et al (24).…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations